Design of a field-portable low power personal data logger - A hardware perspective - Pitts, David G. (Cranfield University, 2008)
There are a vast number of field–portable data loggers currently on the market. They differ greatly in terms of capability and complexity, in many cases being application or function specific. A survey was undertaken to identify market trends and future developments, system hardware specifications and the technologies employed. After comparing system specifications, it was apparent that there was a strong correlation between system performance and power consumption - high performance systems tend to be power hungry, and are typically larger and heavier than their lower performance counterparts. The aim of this project was to design the core of an advanced, flexible, low-power portable data acquisition system, a ‘personal’ data logger (PDL), suitable for medical or athletic performance monitoring. The pocket-sized target system should be capable of high performance - sampling daily or up to 20,000 samples per second – with low power operation, and should be able to measure both analogue and digital signals. The data must be stored in a high-capacity non-volatile memory card, with USB and RS-232 ports provided for data upload and system configuration. With the design specification defined, low power design techniques and the various battery and power supply options were investigated. A survey of system components was carried out and suitable low-power parts identified and selected for the design. After checking the project schematics, the circuit board was designed, manufactured and carefully assembled, ready for function and performance testing. The test results indicated that the project met the design specification, demonstrating its potential for use in a small portable personal data logger. Further work would be required to refine the power supply and power management systems, add an interface board housing a real-time clock, analogue signal conditioning, and input and output connectors, and to develop embedded system software.